A visao paradigmatica da China como grande potencia - Gonçalves, Arnaldo (Relaciones Internacionales, 2018)
El prestigioso académico portugués, residente en Macao, pone sobre la mesa de debate una de las cuestiones que hoy más atraen la atención de los analistas internacionales: El rol actual de China y su proyección futura como gran potencia mundial, que quizás un día cuestione el liderazgo global de los propios Estados Unidos. Desde su punto de vista, el "ascenso pacífico" de China revela una intención de ese país por presentarse como un país confiable pero que sin embargo genera muchas inquietudes en el resto del planeta. The distinguished portuguese academic, Macao resident, proposes to analize one of the issues that is attracting today the attention of most of the international specialists: The present role of China and its future projection as a big World power, that, in the future, can question the sole leadership of the U.S. From his point of view, the "pacific ascension" of China reveals the intention of that country to show himself as a credible country but, however, that creates in the rest of the world some doubts about its real intentions.